Islam at the crossroads understanding its beliefs, history and conflicts - Marshall, Paul A. 1948-; Green, Roberta; Gilbert, Lela (Grand Rapids, MI Baker, 2002)
Inlcudes bibliographical references.
Keywords: Islam -- introductions